Efektivitas Seduhan Daun Yakon (Smallanthus sonchifolius) terhadap Kadar Low Density Lipoprotein (LDL) dan High Density Lipoprotein (HDL) pada Tikus Diabetik yang Diinduksi Streptozotocin (The Efectivity of Yacon Leaves (Smallanthus sonchifolius) Infusion to Low Density Lipoprotein (LDL) and High Density Lipoprotein (HDL) Level in Diabetic Rats Induced by Streptozotocin) - Vitta Permata Sarie; Roedy Budirahardjo; Budi Yuwono (Pustaka Kesehatan, 2015)
Diabetes mellitus (DM) is a metabolic disorder characterized by elevated level of blood glucose abnormalities associated with the metabolism of carbohydrates,lipids and proteins. Lipids metabolism disorder can increase LDL and lower HDL level. One of plants in Indonesia, that has potential as antihyperglycemic and hypolipidemic agent is yakon (Smallanthus sonchifolius) containing chlorogenic acid (CGA). This study aimed to determine the effect of yacon leaves infusion to LDL and HDL level in diabetic rats induced by streptozotocin (STZ). This study was an experimental research laboratories with the post test only control group design. Rats checked the blood glucose early then induced by STZ with dose 65 mg / kg BW. At 3 days post injection, they were checked the blood glucose. Then the rats were divided into 2 groups the control and treatment group. The treatment group was given yacon leaves infusion ( 3.6 ml/200 g BB rats ) for 14 days. Then they were checked LDL and HDL level by using electrospectrofotometer. Statistical analysis showed that there were significant differences in LDL level and no significant difference in HDL level. It could be concluded that the yacon leaves infusion could lower LDL level in diabetic rats induced by STZ, while HDL level had not change. Keywords: Diabetic, HDL, LDL, yacon